2014
DOI: 10.1111/bph.12903
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathways and mechanisms of protection in pre‐ and postconditioning: historical perspective and lessons for the future

Abstract: Ischaemic pre-and postconditioning are potent cardioprotective interventions that spare ischaemic myocardium and decrease infarct size after periods of myocardial ischaemia/reperfusion. They are dependent on complex signalling pathways involving ligands released from ischaemic myocardium, G-protein-linked receptors, membrane growth factor receptors, phospholipids, signalling kinases, NO, PKC and PKG, mitochondrial ATP-sensitive potassium channels, reactive oxygen species, TNF-α and sphingosine-1-phosphate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 198 publications
2
113
0
10
Order By: Relevance
“…Recently, we also demonstrated that the NO-independent sGC activator, cinaciguat, induced PKG-dependent generation of H 2 S from CSE in the mouse heart [42]. In addition, several studies have demonstrated the cardioprotective effects of PKG modulation or activation prior to I/R injury or at the time of reperfusion [3,6,10,32]. The benefits of PKG were not restricted to I/R injury since gene transfer of PKGIb was shown to enhance the antihypertrophic effects of NO in neonatal rat cardiomyocytes [48].…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we also demonstrated that the NO-independent sGC activator, cinaciguat, induced PKG-dependent generation of H 2 S from CSE in the mouse heart [42]. In addition, several studies have demonstrated the cardioprotective effects of PKG modulation or activation prior to I/R injury or at the time of reperfusion [3,6,10,32]. The benefits of PKG were not restricted to I/R injury since gene transfer of PKGIb was shown to enhance the antihypertrophic effects of NO in neonatal rat cardiomyocytes [48].…”
Section: Discussionmentioning
confidence: 90%
“…It is well established that the short washout/reperfusion period applied during the triggering phase of B2PC and IPC, prior to onset of index ischemia, is an essential element in the cardioprotection elicited by these preconditioning modalities . Previous studies from our laboratory showed that the short cycles of ischemia/reperfusion in the case of IPC are characterized by cyclic elevation in tissue cAMP and PKA activation as well as cyclic increases in cGMP levels, suggesting the involvement of the beta‐adrenergic signal transduction system and NO as triggers of IPC‐mediated cardioprotection in the model used.…”
Section: Discussionmentioning
confidence: 93%
“…The opening of mitochondrial K ATP is related to electrochemical changes in the mitochondrial matrix that are responsible for an increased ROS production reported to occur mainly (but not exclusively) at the postischemic reperfusion. ROS can directly activate the PKC isoforms whose contribution to protection is species‐dependent, with PKCε being responsible for protection in the rodent heart, PKCα in large mammals, whereas controversial data are available about PKC (Cohen & Downey, ; Heusch, ). Activated PKC phosphorylates several downstream targets, among which connexin 43 (Cx43) plays a critical role in transferring the protective signal to mitochondria (recently reviewed by Boengler & Schulz, ).…”
Section: The Signal Transduction Of Ipcmentioning
confidence: 99%
“…Adenosine, bradykinin, and opioids are triggers that act on G protein-coupled receptors which, in turn, activate protein kinase C (PKC). Although the pathways are slightly different, they all converge on the PKC, the blockade of which results in the lack of any possible protection attributable to those triggers (Cohen & Downey, 2015). At variance, both exogenous (Nakano, Liu, Heusch, Downey, & Cohen, 2000) and endogenous (Cohen, Yang, & Downey, 2006;Krieg et al, 2009) NO can trigger myocardial protection in a receptor-independent manner; in this case, protection occurs either dependent or independent of the activation of protein kinase G (PKG) signaling pathway (Sun et al, 2013).…”
Section: The Triggersmentioning
confidence: 99%